A Discourse Viewpoint on Visual Semiotics and Ideological Messages in English Textbooks for Secondary Schools - Dias Andris Susanto (English Department, Universitas Negeri Surabaya, 2025)
English books have a big influence on students’ linguistic ability and way of thinking. Beyond verbal information, visual components included in textbooks act as semiotic tools for expressing political and cultural ideas. This investigation looks into how visual semiotics create and communicate political ideas in Indonesian secondary school English literature. Using a qualitative descriptive approach, this study examines Kress and van Leeuwen’s (2006) Visual Grammar framework from a discourse-analytic angle. Intententionally chosen were two often used national curriculum textbooks. Backed by contextual interpretation and sociopragmatic reflection, the study examined representational, interactive, and compositional metafunctions of photographs. Visual cues sometimes stand for Western cultural hegemony, gender stereotyping, and urban-oriented lifestyles, according to research results. Although some visuals encourage inclusiveness and multiculturalism, others subtly strengthen the unequal power dynamics between regional and world identities. Color, gaze, spatial positioning, and symbol choice reveal subtle ideological leanings favoring globalization and modernity discourses. These graphic decisions imply that English books function not only as linguistic objects but also as ideological tools influencing pupils’ views of culture and identity. Pedagogically, knowing semiotic meanings helps instructors to direct their classroom discussions and critical material analysis.